Women Judges in the Muslim World A Comparative Study of Discourse and Practice - Sonneveld, Nadia; Lindbekk, Monika (Women and Gender: The Middle East and the Islamic World, 2017)
Women Judges in the Muslim World: A Comparative Study of Discourse and Practice offers a socio-legal account of public debates and judicial practices surrounding the performance of women as judges in eight Muslim-majority countries. Readership: Scholars, students, and practitioners interested in Law, Middle East Studies, Southeast Asia Studies, Gender, and Religious Studies will find this an indispensable resource.